Kings, gods & spirits from African mythology - Knappert, Jan.; Pelizzoli, Francesca (New York : P. Bedrick, 1995)
A collection of African myths, legends and fables about gods, spirits, ghosts, heroes, and animals.
Originally published: New York : Schocken Books, 1986.
Includes bibliographical references (p. 90) and index.
Horn Book.
School Library Journal.
Wilson's Junior High School.
6.6
Keywords: Mythology, African; African mythology